Serum Chloride Is Inversely Associated With 3 Months Outcomes in Chinese Patients With Heart Failure, a Retrospective Cohort Study - Fu, Zhiqing; An, Li; Lu, Xiaochun; Sheng, Li; Liu, Hongbin (Frontiers in Cardiovascular Medicine, 2022)
Background: Serum chloride was recently found to be associated with prognosis of heart failure (HF) in western countries. However, the evidence was scarce in Asia. We aimed to investigated the relationship between serum chloride and clinical outcomes in a Chinese cohort with hospitalized HF. Methods: We retrospectively analyzed the data from PhysioNet, involving 1996 patients who were admitted with HF between December 2016 and June 2019. Outcome was a composite endpoint of all-cause death or rehospitalization at 3 months. Results: The incidence of the composite endpoint was 26.8% (535/1996); it was 32.2% (213/662), 25.0% (165/661) and 23.3% (157/673) by chloride tertiles (from the lowest to the highest), respectively. The serum chloride at admission was independently and inversely associated with the risk of the composite endpoint (hazard ratio [HR]: 0.967; 95% confidence interval [CI]: 0.939 to 0.996; p=0.026) in contrast to sodium levels, which were no longer significant (p>0.05) after multivariable adjustment. The use of covariate adjustments and subgroups analyses renders our findings robust. Conclusions: Low serum chloride at admission was associated with poor outcomes in Chinese hospitalized patients with HF. These findings warrant future studies for tackling the potential pathophysiological mechanisms and correction methods of hypochloremia in HF.